State Recognition and Democratization in Sub-Saharan Africa: A New Dawn for Chiefs? - Buur, Lars; Kyed, Helene Maria (Governance, Security and Development, 2007)
State Recognition and Democractization in Sub-Saharan Africaآ explores the link between liberal-style democratization and state recognition of traditional authority in Sub-Saharan Africa. Being critical and empirically grounded, the book explores the complex, often counter-balancing consequences of the involvement of traditional authority in the wave of democratization and liberal-style state-building that has rolled over sub-Saharan Africa in the past decade. It scrutinizes how, in practice, traditional leaders are being drawn into governance in Mozambique, Zambia, Namibia, Malawi, Burkina Faso, and the Somali region of Ethiopia, and relates these developments to state governance in the declining democracy of Zimbabwe and the emerging state of Northern Somalia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; authority / autoridade; decentralization / descentralização; governance / governação

Concept Paper on Decentralisation and Local Governance. Module 1: definitions and concepts. - Olsen, Hans Bjørn (Concept paper, 2007)
SDC has been implementing projects in support to decentralisation and local governance for about 15 years. Today, arounf 2/3 of SDC's country programmes include a support to local governance and/or decentralisation. For this reason, an independent evaluation of  SDC’s achievements on “Decentralisation  and local governance” took place in 2006‐2007. One of the recommendations of this evaluation  was to  carry out  a capitalisation of SDC’s experiences in this field. SDC’s  Governance  Division has been charged with implementing this recommendation and  has planned a two‐step process: first to clarify concepts; and secondly, to identify SDC’s practical lessons learnt in this field.  The present document has 3 main objectives: ‐To further a common understanding about concepts linked to decentralisation and local governance  within SDC (HQs and field). ‐ To give basic conceptual elements for capacity building activities in decentralisation ‐ The document does not pretend to be an academically precise paper, but rather a short and succinct  presentation of the various concepts. Therefore, this document does  not  present  a collection of practical experiences from SDCs many  interventions in developing countries, but is the 1st  module of a series of two documents. The 2nd  module  will be published  at the  end of 2008 and will include  practical and concrete recommendations and tips,  which will compiled at the capitalisation workshop of SDC’s experiences in supporting decentralisation  and local governance processes (planned for June 2008).
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; decentralization / descentralização; governance / governação